Comparison of the inactivation capacity of various UV wavelengths on SARS-CoV-2 - Ryosuke Matsuura; Chieh-Wen Lo; Takayo Ogawa; Masaru Nakagawa; Masami Takei; Yasunobu Matsumoto; Satoshi Wada; Yoko Aida (Biochemistry and Biophysics Reports, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a worldwide pandemic. Ultraviolet (UV) is regarded as a very powerful tool against SARS-CoV-2. However, the inactivating effects of different UV wavelengths on SARS-CoV-2 under the same conditions have hardly been compared. Here, we showed that SARS-CoV-2 cultured in Dulbecco's modified Eagle's medium and 2% fetal bovine serum was efficiently inactivated by irradiation with 222, 254, and 265 wavelengths UV, but not at 308 nm. In addition, it was revealed that UV absorption by DMEM-2% FBS is very efficient at 222 nm. Our results present potentially important information for selecting the optimum UV wavelength according to the application.